Resin tag length of one-step and self-etching adhesives bonded to unground enamel - Sundfeld, Renato Herman [UNESP]; Oliveira, Carlos Henrique de [UNESP]; Silva, Adriana Maria Jorge Dal'acqua da [UNESP]; Briso, André Luiz Fraga [UNESP]; Sundfeld, Maria Lúcia Marçal Mazza [UNESP] (Tokyo Dental College, 2005)
Length of resin tags yielded by utilization of an one-step conventional adhesive system and self-etching adhesive system on unground enamel was observed. In study Groups I and III, the enamel surface was etched for 60 seconds with 35% phosphoric acid gel and adhesive systems PQ1 (Ultradent Products, Inc) and Adper Prompt L Pop (3M/ESPE) were applied. Adper Prompt L Pop (3M/ESPE) was also applied in Group II in accordance with the manufacturer's recommendations. After application of these adhesive systems to dental enamel, specimens were prepared for light microscopy analysis to ascertain degree of penetration (x400). The results were submitted to an analysis of variance at the 5% level; whenever there was significance, the Tukey test was applied at the 5% level. It was found that acid etching prior to application of conventional and self-etching adhesive materials provided higher penetration of the adhesive into the unground enamel surface compared to that achieved solely by application of self-etching adhesive.
Keywords: Unground enamel; Conventional adhesive system; Self-etching adhesive system; Light microscopy analysis; Resin tags